2022
DOI: 10.1108/jarhe-03-2021-0117
|View full text |Cite
|
Sign up to set email alerts
|

The mediating effects of student satisfaction on technostress–performance expectancy relationship in university students

Abstract: PurposeThis study aimed to explore the technostress effects on the students' expectancy in their academic performance. Three main factors were used as predictors, namely techno-complexity (TC), techno-insecurity (TIS) and techno-overload (TO), to measure the students' performance expectancy via the mediating effects of student satisfaction (SS).Design/methodology/approachA total of 234 survey-based online questionnaires were filled by students from Universiti Teknologi Mara (UiTM). Based on the data, the hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…Work-Life Balance  Employee Well-being  Job Performance 0,16 0,66 0,1056 Full Mediation findings are consistent with the research conducted by several other researchers where technostress was found to have no significant effect and had a positive path (Aziz et al, 2023;Maipita et al, 2023;Tarafdar et al, 2019). These findings indicate that employees in this study demonstrate the ability to effectively cope with and overcome technostress, mitigating its negative impact on the performance of SOEs employees.…”
Section: H7dsupporting
confidence: 86%
“…Work-Life Balance  Employee Well-being  Job Performance 0,16 0,66 0,1056 Full Mediation findings are consistent with the research conducted by several other researchers where technostress was found to have no significant effect and had a positive path (Aziz et al, 2023;Maipita et al, 2023;Tarafdar et al, 2019). These findings indicate that employees in this study demonstrate the ability to effectively cope with and overcome technostress, mitigating its negative impact on the performance of SOEs employees.…”
Section: H7dsupporting
confidence: 86%
“…Science and technology governance and technology-focused ethics discussions have as one goal to decrease the appearance of new social stressors and to decrease the presence of already existing social stressors as a consequence of scientific and technological advancements [39]. The term technostress reflects technology-induced stress [99][100][101][102][103][104][105][106]. It is argued that more studies are needed that link social stress to the automation literature [71].…”
Section: Social Stressors and Science And Technologymentioning
confidence: 99%
“…It is well known that technologies can cause stress. The term technostress was coined to flag technology-based stress [99][100][101][102][103][104][105][106]. It is argued that more studies are needed that link social stress and automation literature [71].…”
Section: Science and Technology Governance And Ethics And Stress* And...mentioning
confidence: 99%
“…Due to these modernized approaches and demands in educational operations, the level of stress among learners becomes inclined and most researchers often overlook technological stress or better known as Technostress one of the factors that may affect students' performance (Abd Aziz & Abu Yazid, 2021). The management of higher education institutions placed high expectations on students' digital learning abilities (Abd Aziz et al, 2023). However, due to the advanced technology used in the learning process, students faced difficulties which lead the universities unable to identify the levels and types of stress suffered by them and affect their academic performance (Abd Aziz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The management of higher education institutions placed high expectations on students' digital learning abilities (Abd Aziz et al, 2023). However, due to the advanced technology used in the learning process, students faced difficulties which lead the universities unable to identify the levels and types of stress suffered by them and affect their academic performance (Abd Aziz et al, 2023).…”
Section: Introductionmentioning
confidence: 99%